Synthesis and Properties of Core–Shell Metal–Ceramic Microstructures and their Application as Heterogeneous Catalysts. Issue 9 (24th July 2014) - Kim, Jieun; Lee, Doohwan
Abstract A facile synthesis of core–shell metal–ceramic microcomposites with unique structural and chemical properties and their superior performance as heterogeneous catalysts are reported. These core–shell microstructures were prepared by hydrothermal surface oxidation of Al particles in water with or without the presence of heterometal species followed by calcination. The crystalline porous MgAl2O4 spinel, which has complex morphological features, allowed the superior dispersion and stability of Rh clusters, and the core–shell microarchitecture provided facilitated heat and mass transport concomitantly, which enabled a significant enhancement in the glycerol conversion turnover rate to hydrogen compared to the conventional Rh/MgAl2O4 catalyst. This simple and scalable heterogeneous catalyst design approach offers practical applicability for catalytic reactions that require extensive heat and mass flux and rapid process response, such as for micro‐fuel‐processing in fuel cells.